Effect of salinitu and sodicity on Bacterial-Plant symbiotic relationship - Fiatori, Mikaeel Y; El-Hassan, Gadalla A; El-Mahi, Youssif E (Al-Mukhtar Journal of Sciences, 1996)
A green house pot experiment using CBD was conducted to study the effect of increasing levels of salinity and sodicity on symbiotic relationship between faba bean plant Vicia faba and Rhizobium spp. using CBD technique. The planats were grown and inoculated with the rhizobium strain (R. leguminosarum b.v. viceae) which was isolated from the same soil on which the study was carried out, and the plants were irrigiated with water of salinity levels (EC=2,4 and 6 ms. cml) and sodicity levels (SAR + 10,20 and 30 (meq.1-1)1/2 at each level of salinity. The results of the study showed that the dry weights of shoot and root systems and the plant heights were significantly reduced with incerease of salinity (EC=6 ms. cm') Compared with the Control. On the other hand, no clear effect was observed for increasing sodicity from SAR=10 to 30 (mea. 1-)1/2, but the dry weights of shoot and roots at the three levels of SAR were significantly lower compared with the control. The Study also indicated that the nodule numbers were adversely affected by increasing levels of salinity. However, the nodule numbers were significantly increased with SAR=30 (meq. 1-?)1/2. compared to other SAR treatments. Considering the total absorbed nitrogen, however, no significant differences were shown with respect to increasing level of SAR and the control, but significant differences were observed only between EC=6 and the control.